The energy transitions index: An analytic framework for understanding the evolving global energy system. (November 2019) - Singh, Harsh Vijay; Bocca, Roberto; Gomez, Pedro; Dahlke, Steve; Bazilian, Morgan
Abstract: The question of how to enable an effective, modern, global energy transition is garnering significant interest in both academic and policy making communities. Composite statistical indices have emerged as a useful class of tools to offer policymakers additional insights into the state and trajectory of energy transitions around the world. In this commentary, we discuss the purpose of energy indices in general and document several prominent examples. We then introduce and place in this landscape the World Economic Forum's Energy Transitions Index (ETI). The ETI is a tool for energy decision makers that strives to be a comprehensive, global index that tracks the performance of energy systems at the country level. It also incorporates macroeconomic, institutional, social, and geopolitical considerations that provide enabling conditions for an effective energy transition. In this way, the ETI enables a better understanding of the past and present states of energy transition around the world, leading to more informed energy transition policies and investment decisions. Highlights: Composite indices are a useful tool to understand the energy transition. The World Economic Forum's Energy Transitions Index (ETI) is one example. The ETI measures countries' energy system performance and transition readiness.